2010
DOI: 10.3346/jkms.2010.25.1.155
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report with Lymphangiomatosis of the Colon

Abstract: The incidence of lymphangiomas in the gastrointestinal tract is low, particularly in the colon and rectum, and most cases are solitary. Lymphangiomatosis of the colon are encountered infrequently with only one report in the English literature, and polypectomy was performed for the diagnosis in that case report. However, trends in the diagnosis of lymphangiomatosis of colon have been changing since the development of endoscopic ultrasonography (EUS), and this case is the first in that lymphangiomatosis of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…We administered a small intestinal fiberscopy, which clearly revealed the pathological changes of the intestine that could explained why this patient had hypoproteinemia. Aggressive surgery should be avoided in these symptomless cases because it is now known that these lesions are benign [9] . Kochman et al [10] suggested that asymptomatic lymphangiomas should most likely be left alone.…”
Section: Discussionmentioning
confidence: 99%
“…We administered a small intestinal fiberscopy, which clearly revealed the pathological changes of the intestine that could explained why this patient had hypoproteinemia. Aggressive surgery should be avoided in these symptomless cases because it is now known that these lesions are benign [9] . Kochman et al [10] suggested that asymptomatic lymphangiomas should most likely be left alone.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic lymphangioma used to be considered an extremely rare disease, but recently, along with the increasing prevalence of endoscopy and endoscopic ultrasound (EUS), it has become more commonly encountered and has been reported more frequently (5,6). There are several reports on the use of EUS for the diagnosis of colonic lymphangioma (4,6). The present study reports a case of colonic lymphangiomatosis manifested as recurrent bowel bleeding, which was diagnosed by EUS and treated with laparoscopic segmental sigmoid colon resection.…”
Section: Introductionmentioning
confidence: 93%
“…The majority of lymphangiomas usually occur in the head, neck regions and axillary areas, but rarely in the colon (2)(3)(4). Colonic lymphangioma used to be considered an extremely rare disease, but recently, along with the increasing prevalence of endoscopy and endoscopic ultrasound (EUS), it has become more commonly encountered and has been reported more frequently (5,6). There are several reports on the use of EUS for the diagnosis of colonic lymphangioma (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…Generalised lymphangiomatosis is usually associated with visceral and osteolytic involvement and poor prognosis (9). It is also increasingly being recognized in the setting of the colon with increased use of endoscopic ultrasonography (10).…”
mentioning
confidence: 99%